Karakteristik Set Yogurt Sinbiotik dengan Penambahan Variasi Konsentrasi Ekstrak Kacang Hijau - Alawiyah, Iin Siti Siti; M, Mardiana; Tubagus, Robi; Quddus, Ati Atul (Jurnal Pangan dan Gizi, 2024)
Synbiotic set yogurt with the addition of mung bean extract has the potential as an alternative functional food that can meet the needs of people who want to have a healthy life. Mung beans are a source of prebiotics because they contain oligosaccharides in the form of raffinose and stakiose. The addition of mung bean extract concentration in the synbiotic set yogurt aims to determine the effect of increasing the concentration of mung bean extract on the microbiological, chemical, and acceptability characteristics of the synbiotic set yogurt and determine the concentration of mung bean extract that produces the best synbiotic set yogurt based on SNI. This study used a completely randomized design (CRD) with four treatments, namely P1 (15% mung beans extract), P2 (20% mung beans extract), P3 (25% mung beans extract) and P4 (30% mung beans extract). Based on the results of the research that has been done, it can be concluded that the addition of mung bean extract to the synbiotic set yogurt has a significant effect on microbiological values (prebiotics, pH, and total lactic acid bacteria), acceptability values (taste, color, texture, and overall attributes) and chemical values (ash and lactic acid content). But not significantly different from the aroma attribute. The best concentration of synbiotic set yogurt with the addition of varying concentrations of mung bean extract is found in treatment P1 (mung bean extract 15%), namely prebiotic levels of 2.6 x 108 CFU/ml, pH 3.83, total Bal 3.2 x 107 CFU/ml, ash content 0.73%, total lactic acid 0.54%, taste 1.84, aroma 2.16, color 1.60, texture 1.72 and overall 1.84